Lipschutz ulcer - Nonsexual acute genital ulceration in a 10-year-old girl - S R Radhika; Kanathur Shilpa; H V Shree Lakshmi; T N Revathi (Wolters Kluwer Medknow Publications, 2021)
Acute genital ulcers are painful and distressing. Lipschutz ulcer (LU), also known as ulcus vulvae acutum, is a rare and underdiagnosed entity presenting as an acute painful vulvar ulcer in young women. Although the etiology is not known, recent reports have associated it with infections such as Epstein-Barr virus, cytomegalovirus (CMV), Mycoplasma pneumoniae, Mycoplasma fermentans, mumps, and parvovirus B19. The diagnosis is made by exclusion, after ruling out the usual causes of genital ulcerations such as sexually transmitted diseases, autoimmune causes, trauma, drug reactions, and local manifestations of systemic illnesses. We report the case of a 10-year-old girl who developed flu-like symptoms, followed by painful vulvar ulcers within 2 days. Lipshutz ulcer must br considered among the causes of genital ulcers.